Acquired thermo-tolerance and trans-generational heat stress response at flowering in rice - Shi, W.; Lawas, L. M. F.; Raju, B.R.; Jagadish, S.V.K. (Wiley, 2016)
In rice, pre‐exposure to sublethal treatment followed by harsh lethal treatment is known to improve tolerance of different abiotic stresses at the vegetative stage within and across generations. Our major aim was to test the phenomenon of thermo‐tolerance at flowering across (trans)‐generations and within generation using rice cultivars contrasting for heat stress tolerance at flowering. To test trans‐generational response, plants were exposed to higher temperature at flowering stage and seeds obtained from previous generations were exposed to heat stress during flowering, which recorded significantly lower fertility when exposed to the same degree of stress in their subsequent generations. A pre‐acclimation to moderately high acclimating temperatures imposed over three different durations during the vegetative and initial reproductive stage showed positive response in the tolerant N22, particularly under severe heat stress (40 °C). This finding indicates the possibility of acquiring ameliorative thermo‐tolerant mechanisms at anthesis, restricted to tolerant genetic backgrounds to combat subsequent harsh conditions within the same generation. However, trans‐generational memory was ineffective in mitigating spikelet sterility losses in both tolerant and susceptible backgrounds. Rice is extremely sensitive to heat stress during flowering; hence, similar exercise across other crops of interest needs to be carried out before generalizing conclusions.